2011
DOI: 10.1080/00380768.2011.567398
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity and silicon on root characteristics, growth, water status, proline content and ion accumulation of purslane (Portulaca oleraceaL.)

Abstract: In order to study the effects of salinity and silicon application on root characteristics, growth, proline content, leaf and root ion accumulation of purslane (Portulaca oleracea L.), a greenhouse experiment was conducted at Ferdowsi University of Mashhad, Iran. The experiment was carried out in a split plot design in which levels of salinity (0, 120 and 240 mM) were allocated as main plots and silicon application of 1 mM sodium silicate and no application assigned as subplots with three replications. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(63 citation statements)
references
References 23 publications
9
54
0
Order By: Relevance
“…141 Silicon (Si) is the second most abundant mineral element in the soil and the ability of Si to ameliorate the negative effect of sodium chloride (NaCl) on plant growth rate is well documented. 139 By application of Si fresh and dry weights, root volume, and chlorophyll concentration increased furthermore, photosynthesis rate, mesophyll conductance and plant water use efficiency were enhanced under salinity stress condition. 141 Pessarakli et al, 142 and Pessarakli & Touchane 143 examined bermudagrass 143,144 cv.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…141 Silicon (Si) is the second most abundant mineral element in the soil and the ability of Si to ameliorate the negative effect of sodium chloride (NaCl) on plant growth rate is well documented. 139 By application of Si fresh and dry weights, root volume, and chlorophyll concentration increased furthermore, photosynthesis rate, mesophyll conductance and plant water use efficiency were enhanced under salinity stress condition. 141 Pessarakli et al, 142 and Pessarakli & Touchane 143 examined bermudagrass 143,144 cv.…”
mentioning
confidence: 99%
“…Salt stress reduced CO 2 concentration around the stomata, diminished cell membrane permeability for CO 2 , reduced the sink capacity of the leaves, and in turn, reduced photosynthesis activity. 139,140 Under salinity condition, fresh and dry weights, root volume, stem diameter, sub stomatal CO 2 , photosynthetic rate, mesophyll conductance, and photosynthetic water use efficiency all reduced, but electrolyte leakage increased by increasing salinity levels in cherry tomatoes. 141 Silicon (Si) is the second most abundant mineral element in the soil and the ability of Si to ameliorate the negative effect of sodium chloride (NaCl) on plant growth rate is well documented.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, silicon (Si) application can be performed, since it may increase the plant's tolerance to elevated temperatures (Okamoto, 1969;Soundararajan et al, 2014), hydric deficit (Lux et al, 2002;Hattori et al, 2005), Mg toxicity (Galvez et al, 1987) e Al toxicity (Cocker et al, 1998) and salinity (Kafi and Rahimi, 2011). Silicon is absorbed by sorghum as opaline silicon (phytolites), increasing the growth rates and, therefore, crop production.…”
Section: Introductionmentioning
confidence: 99%
“…Salt (salinity) stress may also affect electron transport, photophosphorylation and enzymatic activities (Fadzilla et al 1997 ;Liang 1999 ;Steduto et al 2000 ). Inclusion of Si has widely been reported to signifi cantly increase the growth of many plant species through increasing photosynthetic activity, leaf area and chlorophyll content and improving chloroplast structure in salt-stressed plants (Liang et al 1996 ;Liang 1998 ;Yeo et al 1999 ;Al-Aghabary et al 2004 ;Zhu et al 2004 ;Romero-Aranda et al 2006 ;MurilloAmador et al 2007 ;Tuna et al 2008 ;Savvas et al 2009 ;Hashemi et al 2010 ;Lee et al 2010 ;Tahir et al 2012 ;Kafi and Rahimi 2011 ;Bae et al 2012 ;Yin et al 2013 ;Soundararajan et al 2013 ;Haghighi and Pessarakli 2013 ). Indeed, Liang et al ( 1996 ) showed that the addition of Si could signifi cantly enhance dry matter yields of both salt-sensitive (cv.…”
Section: Photosynthetic Parameters and Plant Growthmentioning
confidence: 98%